Decadal-interdecadal climate variability over Antarctica and linkages to the Tropics : analysis of ice core, instrumental, and tropical proxy data - Okumura, Yuko; Schneider, David; Deser, Clara; Wilson, Rob (Journal of Climate, 2013)
The Antarctic continent contains the majority of the global ice volume and plays an important role in a changing climate. The nature and causes of Antarctic climate variability are, however, poorly understood beyond interannual time scales due to the paucity of long, reliable meteorological observations. This study analyzes decadal-interdecadal climate variability over Antarctica using a network of annually resolved ice core records and various instrumental and tropical proxy data for the 19th and 20th centuries. During the 20th century, Antarctic ice core records indicate strong linkages to sea surface temperature (SST) variations in the tropical Pacific and Atlantic on decadal-interdecadal time scales. Antarctic surface temperature anomalies inferred from the ice cores are consistent with the associated changes in atmospheric circulation and thermal advection. A set of atmospheric general circulation model experiments supports the idea that decadal SST variations in the tropics force atmospheric teleconnections that affect Antarctic surface temperatures. When coral and other proxies for tropical climate are used to extend the analysis back to 1799, a similar Antarctic-tropical Pacific linkage is found, with evidence for a weaker connection during the first half of the 19th century. Over the past 50 years, a change in the phase of Pacific and Atlantic interdecadal variability may have contributed to the rapid warming of the Antarctic Peninsula and West Antarctica and related changes in ice sheet dynamics. Peer reviewed